2013
DOI: 10.1097/aln.0b013e31827dde74
|View full text |Cite
|
Sign up to set email alerts
|

A Single-nucleotide Polymorphism in SCN9A May Decrease Postoperative Pain Sensitivity in the General Population

Abstract: Patients carrying the SCN9A 3312Tallele presented with lower postoperative pain sensitivity in the presence of a similar surgical pain stimulus, and had a lower likelihood of developing inadequate analgesia than those carrying the 3312Gallele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…11,17,45 Thus, the Nav1.7 channel may function to skew pain perception in opposite directions. 15,19 Our data in the current study further supported this concept, demonstrating that different SCN9A SNPs may contribute to the function of the Nav1.7 channel be enhanced or weakened, skewing the state of pain perception in the general population.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 88%
See 2 more Smart Citations
“…11,17,45 Thus, the Nav1.7 channel may function to skew pain perception in opposite directions. 15,19 Our data in the current study further supported this concept, demonstrating that different SCN9A SNPs may contribute to the function of the Nav1.7 channel be enhanced or weakened, skewing the state of pain perception in the general population.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 88%
“…Although some studies have recently investigated the association between SCN9A SNPs and the pain phenotype, 15,22,34,42 most of these studies have focused on only one or certain SNPs, and the participants in these studies often had underlying diseases or chronic pain, which made it difficult to investigate the effects of SCN9A on participants' original pain sensitivity. Thus, in the current study, we used a combined candidate and tag SNP approach to explore possible associations between SCN9A SNPs and basal pain perception, as evaluated by experimental methods in healthy female undergraduates.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, apart from their complete inability to sense pain, loss of smell (anosmia) is the only other sensory impairment in individuals with this channelopathy [90,91]. Moreover, certain polymorphisms in SCN9A correlate with an individual's threshold to various types of pain [92,93]. Thus, there is a strong genetic link between pain and the level of Na V 1.7 activity, indicating that selective blockers of Na V 1.7 are likely to be useful analgesics [94,95].…”
Section: Venom-derived Therapeutics: Focus On Spider Venomsmentioning
confidence: 94%
“…A recent study by Duan et al 19 showed that a SNP lesion in SCN9A may decrease post-operative pain sensitivity in a cohort of patients (Table 2).…”
Section: Sodium-channelopathy and Postoperative Pain Sensitivitymentioning
confidence: 99%